Pecking Order Theory: evidence from Malaysia and Thailand food and beverages industry / Wahida Ahmad and Noor Azillah Mohamad Ali - Ahmad, Wahida; Mohamad Ali, Noor Azillah (Universiti Teknologi MARA, Perlis, 2017)
Capital structure decision is crucial for a firm to ensure credit is not a threat to a firm, instead it acts as a boosting factor for the company growth and survival. Companies commonly refer to the two competing theory, the pecking order theory and the trade-off theory in determining their optimal capital structure. The comparative study is to find evidence of the application of the pecking order theory in food and beverages industry in two countries, Malaysia and Thailand. The paper includes five explanatory variables in determining companies leverage; which are profitability, asset tangibility, growth opportunity, firm size, and liquidity level. Employing the unbalanced panel data, the study estimates the random effect model for Malaysia and the fixed effect model for Thailand. The study covers ten (10) years period from 2004 to 2013 of 37 Malaysian F&B companies and 38 Thailand F&B companies, all are publicly listed in the Bursa Malaysia and the Stock Exchange of Thailand respectively. The results find evidences of the pecking order theory application in both countries. Except for asset tangibility and growth opportunity, findings for Malaysia and Thailand are relatively similar.